Seawater mixing self-adaptive novel cementing material as well as preparation method and application thereof
By using seawater mixing and raising new adaptive cementitious materials under seawater mixing conditions, the problem of poor structural stability of traditional cement concrete in seawater is solved, and the steadily improves strength and improves durability are achieved.
Patent Information
- Application Number
- CN202411598798.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-11
AI Technical Summary
Traditional cement concrete has poor structural stability due to multi-ion erosion in seawater, and even has the problem of inverted strength in the later stage, and lacks new gelling materials that can maintain continuous growth in strength in special marine environments.
Adaptive new type of cementitious cementitious material is made of silicate cement, auxiliary cementitious material, high-belitt sulfa calcium aluminate cement clinker, silicon-aluminum sol composite, nanoparticle stabilizer and appropriate amounts The water reducer is composed of a modified silicon-aluminum sol composite by sonication and added to the mixed powder to improve strength and durability.
This material exhibits high early strength, steady increase in later strength, and strong chloride ion curing in seawater, significantly improving the durability and seawater corrosion resistance of offshore concrete structures.
Smart Images

Figure CN119461911A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cement-based pavement materials, and in particular to a new self-adaptive cementitious material mixed with seawater, and a preparation method and application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] With the rapid development of infrastructure construction in the marine environment, the number and scale of reinforced concrete structures used are large, making high-workability and high-durability marine engineering concrete widely used. However, in the open sea where fresh water resources are scarce, it is necessary to use seawater to mix and maintain cement concrete for construction, which puts forward new requirements for cement concrete. The structural stability of traditional cement concrete deteriorates under the erosion of harmful ions in seawater, and even the problem of strength shrinkage in the later stage occurs. The main reasons include:
[0004] (1) The hydration of silicate cement produces a large amount of Ca(OH)2, which makes it very easy to be dissolved under long-term immersion and scouring in multi-ion seawater solution, resulting in the degradation of the microstructure of cement-based materials.
[0005] (2) In the seawater-mixed cement-based material system, the seawater used for mixing and curing is rich in Cl - Mg 2+ and SO4 2+ As the cement hydration reaction in the concrete structure proceeds, the concrete matrix structure gradually becomes dense. The presence of the above-mentioned ions causes a large amount of expansion phase to be produced in the later stage of cement hydration, causing the concrete matrix to expand and crack, destroying the concrete structure.
[0006] Under the condition of seawater mixing, there is currently a lack of a new type of cementitious material that can maintain continuous growth in strength in the special marine environment and during the process of multi-ion coupling erosion. Summary of the invention
[0007] In view of the fact that current cement concrete materials cannot effectively cope with the erosion problem caused by the coupling of multiple harmful factors in seawater, the present invention provides a new type of seawater-adaptive cementitious material and its preparation method and application, which can achieve steady improvement in strength under seawater mixing and curing conditions, and improve the durability of marine concrete structures in seawater. Specifically, the present invention discloses the technical solution as shown below.
[0008] First, the present invention provides a new self-adaptive cementitious material for seawater mixing, comprising the following components: 30-70 parts by weight of silicate cement, 20-50 parts by weight of auxiliary cementitious material, 5-15 parts by weight of high-belite calcium sulfoaluminate cement clinker and / or high-belite calcium ferroaluminate cement clinker, 6-14 parts by weight of silica-alumina sol complex (DSA), 1-3 parts by weight of water reducer, 3-7 parts by weight of nanoparticle stabilizer, and 28-50 parts by weight of mixing water. The silica-alumina sol complex (DSA) comprises nano silica sol and nano aluminum sol at the same time, and the silica sol is connected to form -COO- by dehydration condensation of Si-OH on its surface and -COOH on the surface of aluminum sol, thereby forming the DSA.
[0009] Furthermore, the auxiliary cementitious material includes at least one of slag powder, fly ash, silica fume, etc. Optionally, the fineness of the auxiliary cementitious material is 200-400 meshes.
[0010] Furthermore, the mass ratio of the nano silica sol to the nano alumina sol is 0.5-1.5:0.5-1.5. Optionally, the particle size of the nano silica sol and the nano alumina sol are both 10-20 nm. The solid content of the nano silica sol and the nano alumina sol are both 20-50%.
[0011] Furthermore, the water reducer includes at least one of a polycarboxylate water reducer, a naphthalene-based water reducer, a lignin sulfonate water reducer, and the like.
[0012] Furthermore, the nanoparticle stabilizer includes at least one of cocamidopropyl betaine, cocamidopropyl hydroxysulfonate ammonium, alkyl acyl imidazoline, etc. The present invention utilizes the characteristics of the nanoparticle stabilizer containing both hydrophilic and hydrophobic groups, and one end of the hydrophilic group is rapidly complexed with the hydrophilic group on the surface of the silica-alumina sol complex (DSA), while the hydrophobic group is exposed on the surface of the DSA, thereby forming a double electric layer and a steric hindrance layer, generating electrostatic repulsion and steric hindrance effects, preventing DSA particles from agglomerating, and keeping the DSA in a stable and uniformly dispersed state.
[0013] Furthermore, the mixing water includes at least one of fresh water, sea water, etc.
[0014] Secondly, the present invention provides a method for preparing the novel self-adaptive gelling material for seawater mixing, comprising the following steps:
[0015] (1) The silicate cement, auxiliary cementitious materials, high-belite calcium sulphoaluminate cement clinker and / or high-belite calcium ferroaluminate cement clinker are mixed to obtain a mixed powder for standby use.
[0016] (2) The nano-silica sol and the nano-alumina sol are mixed and then ultrasonically treated to obtain a silica-alumina sol composite (DSA), wherein the silica sol is dehydrated and condensed by Si-OH on its surface and -COOH on the surface of the aluminum sol to form -COO- to connect the two sol particles.
[0017] (3) The nanoparticle stabilizer is added to the silica-alumina sol complex and mixed to obtain a modified silica-alumina sol complex, and then the complex is added to the mixing water and mixed, and then the mixed powder and the water reducing agent are added and mixed to obtain a cementitious material.
[0018] Furthermore, in step (2), the ultrasonic treatment time is 30 to 90 minutes, and the ultrasonic power is 60 to 100W.
[0019] Finally, the present invention provides the application of the novel self-adaptive cementitious material for seawater mixing in the fields of marine engineering, water conservancy engineering, hydropower engineering, bridge engineering, etc.
[0020] Compared with the prior art, the technical solution of the present invention has at least the following beneficial effects:
[0021] The adaptive new cementitious material mixed with seawater of the present invention has the advantages of high early strength, steady improvement of late strength and strong chloride ion curing, which effectively improves the durability of marine concrete structures in seawater. This is because: the auxiliary cementitious material has the characteristics of secondary hydration reaction, but the start of this hydration reaction is late, so it can start to play a role in the late stage of cement hydration, react with calcium hydroxide produced by cement hydration to form cementitious components such as hydrated calcium silicate (CSH), thereby reducing the content of calcium hydroxide in the concrete structure, and converting it into a cementitious component with cementitious properties, which helps to improve the mechanical properties of the concrete structure, thereby reducing the concrete structure from being soaked and scoured by seawater, causing calcium hydroxide dissolution, and then causing concrete structure damage, strength reduction, and shortened service life. The high activity of the nanoparticle sol can play a role in the early stage of cement hydration, consume the calcium hydroxide produced by hydration, and improve the early strength. Among them, the active silicon component in the silicon-aluminum composite sol (DSA) generates high-density and high-toughness CSH gel and MSH gel components with calcium hydroxide produced by cement hydration and magnesium ions in seawater. The active aluminum component forms a high-strength hydration product calcium sulfoaluminate (AFt) with the sulfate ions in seawater and the cement hydration product calcium hydroxide. At this time, the active silicon component in DSA participates in cement hydration to generate low-calcium silicon ratio CSH gel with a longer chain length, which can effectively resist the cracking stress generated by the expansion of the matrix in the late stage of seawater mixed cement hydration. And because DSA is a silicon-aluminum complex, while generating high-toughness CSH and MSH gels, high-strength AFt is also generated based on the same sol particles. The three are synchronously grown in situ to form a "rigid and flexible" ultra-tough three-dimensional space cross-network structure, and can coat and entangle the chloride ions in seawater, playing a role in solidifying chloride ions. When the high Belite calcium sulfoaluminate cement clinker and / or high Belite calcium ferroaluminate cement clinker are undergoing a hydration reaction, the free sulfate ions in the seawater can be solidified into trisulfide calcium sulfoaluminate (AFt) and monosulfide calcium sulfoaluminate (AFm). The AFm can continue to react with chloride ions in seawater to form Friedel salts, which not only further solidifies the chloride ions, but also avoids the destruction of the concrete structure caused by the later generation of Friedel salts because the Friedel salts are formed in the early stage of hydration of the concrete structure. This is because the process of forming Friedel salts is an expansion process, but as the cement hydration reaction proceeds, the cement matrix gradually becomes dense and the plasticity decreases, and the formation of Friedel salts easily causes the matrix to expand and crack. In addition, the hydration reaction of the high-content high-belite phase in the cement clinker is mainly concentrated in the later stage, which effectively improves the later strength of the concrete structure.
[0022] It can be seen that the mutual coordination of the above components effectively eliminates the internal cause of harmful ion damage to the matrix during seawater mixing and the external cause of harmful ion corrosion during seawater curing, achieving "double protection" against internal and external factors, overcoming the problem that concrete cannot effectively cope with the erosion caused by the coupling of multiple harmful factors in seawater, solving the problem of scarce freshwater resources during ocean construction, and facilitating the implementation of my country's ocean construction strategy. The test results of this embodiment show that the prepared new adaptive cementitious material for seawater mixing has excellent durability, resistance to ion corrosion and mechanical strength. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0024] Figure 1 This is a picture of the silica-alumina sol composite sample prepared in the following Example 1.
[0025] Figure 2 This is a compressive strength test diagram of the specimen prepared in the following Example 1.
[0026] Figure 3 The XRD pattern of the specimen prepared in Example 1 is shown below.
[0027] Figure 4 The following is a SEM image of the test piece prepared in Example 1. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0029] Unless otherwise defined, all professional and scientific terms used in the present invention have the same meanings as those familiar to those skilled in the art. The reagents or raw materials used in the present invention can be purchased through conventional channels. If there are no special instructions, the reagents or raw materials used in the present invention are used in a conventional manner in the art or in accordance with the product instructions. In addition, any method and material similar to or equivalent to the described content can be applied to the method of the present invention. Now, the technical solution of the present invention is further described in conjunction with the accompanying drawings and specific embodiments of the specification.
[0030] The components in each 1 kg of simulated seawater in the following examples are shown in Table 1:
[0031] Table 1
[0032] NaCl <![CDATA[CaCl2]]> KCl <![CDATA[MgCl2]]> <![CDATA[MgSO4]]> Deionized water 28.208g 1.253g 0.722g 1.101g 3.312g 965.404g
[0033] Example 1
[0034] The preparation of a novel self-adaptive cementitious material for seawater mixing includes the following steps:
[0035] (1) Take the following raw material components: 50 parts by weight of 42.5 ordinary Portland cement, 30 parts by weight of auxiliary cementitious materials, 10 parts by weight of high-belite calcium sulfoaluminate cement clinker, 10 parts by weight of silica-alumina sol complex, 1 part by weight of polycarboxylic acid water reducer, 5 parts by weight of nanoparticle stabilizer, and 40 parts by weight of simulated seawater as shown in Table 1 above. Among them, the fineness of the cement (200 mesh residue) is 1.3%, the auxiliary cementitious material is 200 mesh slag powder, and the nanoparticle stabilizer is cocoamidopropyl betaine.
[0036] (2) The silicate cement, auxiliary cementitious material and high-belite calcium sulfoaluminate cement clinker are mixed and stirred for 5 minutes to obtain a mixed powder for use.
[0037] (3) Nano-silica sol and nano-alumina sol were mixed in a mass ratio of 1:1 and then ultrasonically treated for 60 min at an ultrasonic power of 80 W. After the mixture was completed, a silica-alumina sol composite (such as Figure 1 The particle sizes of the nano-silica sol and the nano-alumina sol are both distributed between 10 and 20 nm, and the solid contents of the nano-silica sol and the nano-alumina sol are both 45%.
[0038] (4) adding the nanoparticle stabilizer to the silica-alumina sol complex and stirring evenly to obtain a modified silica-alumina sol complex, then adding the complex to the simulated seawater and stirring evenly, and then adding the mixed powder and the water reducing agent and stirring evenly to obtain a gelling material.
[0039] Performance test: (1) The cementitious material prepared in this embodiment is prepared by mixing the mortar with simulated seawater according to the preparation method of the standard mortar in the "Test Method for Strength of Cement Mortar (ISO Method)" (GBT 17671-2021), pouring it into a mold, demolding it after hardening and forming, and then fully immersing it in seawater and curing it at room temperature. The compressive strength of the specimens at the ages of 1d, 28d, and 100d are tested respectively. Then the compressive strength retention rate and 28d chloride ion migration coefficient of the specimen are tested. Wherein: the compressive strength is tested according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GBT 17671-2021) (such as Figure 2(2) According to the Technical Specification for the Detection of Chloride Ion Content in Concrete (JGJ / T 322-2013), the water-soluble chloride ion content of the cementitious material prepared in this embodiment after hardening for 28 days was measured, and the percentage of the water-soluble chloride ion content in the mass of the cementitious material was calculated. The test results of the above performance indicators are shown in Table 2 below.
[0040] It can be seen that the new self-adaptive cementitious material for seawater mixing prepared in this embodiment has the characteristics of high early strength, steadily improved later strength, strong chloride ion curing ability, and strong resistance to chloride ion and sulfate ion corrosion, showing excellent durability and resistance to seawater erosion.
[0041] Table 2
[0042]
[0043] Figure 3 The XRD patterns of the specimens prepared in this embodiment at the ages of 1d, 28d, and 100d are shown. It can be seen that the Friedel salt peak generated by AFm curing chloride ions begins to appear in the specimen at 1d, and Friedel salt is obviously generated with the increase of curing age. The amount of Friedel salt and AFt generated at the ages of 28d and 100d remains almost unchanged, indicating that the chloride ions have been completely cured at 28d, avoiding the expansion and cracking of the matrix due to the generation of Friedel salt in the later stage, and ensuring the stable improvement of strength.
[0044] Figure 4 This is a SEM image of the specimen prepared in this example at 28 days of age. The hydration products circled in different colors in the figure correspond to the annotations on both sides of the figure. It can be seen that there are Friedel salt, Aft and CSH gel in the specimen, as well as AFm remaining after absorbing chloride ions and converting them into Friedel salt.
[0045] Example 2
[0046] The preparation of a novel self-adaptive cementitious material for seawater mixing includes the following steps:
[0047] (1) Take the following raw material components: 70 parts by weight of 42.5 ordinary Portland cement, 50 parts by weight of auxiliary cementitious materials, 10 parts by weight of high-belite calcium sulfoaluminate cement clinker, 5 parts by weight of high-belite calcium ferroaluminate cement clinker, 14 parts by weight of silica-alumina sol complex, 3 parts by weight of polycarboxylate water reducer, 7 parts by weight of nanoparticle stabilizer, and 50 parts by weight of simulated seawater as shown in Table 1 above. Among them, the fineness of the cement (200 mesh residue) is 1.3%, the auxiliary cementitious material is fly ash with a fineness of 400 mesh, and the nanoparticle stabilizer is cocamidopropyl ammonium hydroxysulfonate.
[0048] (2) The silicate cement, auxiliary cementitious material and high-belite calcium sulfoaluminate cement clinker are mixed and stirred for 5 minutes to obtain a mixed powder for use.
[0049] (3) Mixing nano-silica sol and nano-alumina sol in a mass ratio of 0.5:1.5 and then ultrasonically treating for 30 minutes at an ultrasonic power of 100 W to obtain a silica-alumina sol composite. The particle sizes of the nano-silica sol and the nano-alumina sol are both distributed between 10 and 20 nm, and the solid contents of the nano-silica sol and the nano-alumina sol are both 20%.
[0050] (4) adding the nanoparticle stabilizer to the silica-alumina sol complex and stirring evenly to obtain a modified silica-alumina sol complex, then adding the complex to the simulated seawater and stirring evenly, and then adding the mixed powder and the water reducing agent and stirring evenly to obtain a gelling material.
[0051] Performance test: The same method as in Example 1 was used to test the compressive strength of the test pieces of the cementitious material prepared in this example at ages of 1d, 28d, and 100d, the compressive strength retention rate of the test piece at age of 28 after being immersed in seawater for 100 days, the chloride ion migration coefficient, and the water-soluble chloride ion content of the cementitious material after hardening, and the percentage of the content of the chloride ion in the mass of the cementitious material was calculated. The test results of the above performance indicators are shown in Table 3 below.
[0052] It can be seen that the new self-adaptive cementitious material for seawater mixing prepared in this embodiment has the characteristics of high early strength, steadily improved later strength, strong chloride ion curing ability, and strong resistance to chloride ion and sulfate ion corrosion, showing excellent durability and resistance to seawater erosion.
[0053] Table 3
[0054]
[0055] Example 3
[0056] The preparation of a novel self-adaptive cementitious material for seawater mixing includes the following steps:
[0057] (1) Take the following raw material components: 30 parts by weight of 42.5 ordinary Portland cement, 20 parts by weight of auxiliary cementitious material, 5 parts by weight of high-belite calcium aluminoferrocement clinker, 6 parts by weight of silica-alumina sol complex, 2 parts by weight of sodium lignin sulfonate water reducer, 3 parts by weight of nanoparticle stabilizer, and 28 parts by weight of simulated seawater as shown in Table 1 above. Among them, the fineness of the cement (200 mesh residue) is 1.3%, the auxiliary cementitious material is silica fume, and the nanoparticle stabilizer is alkyl acyl imidazoline.
[0058] (2) The silicate cement, auxiliary cementitious material and high-belite calcium sulfoaluminate cement clinker are mixed and stirred for 5 minutes to obtain a mixed powder for use.
[0059] (3) Mixing nano-silica sol and nano-alumina sol in a mass ratio of 1.5:0.5 and then ultrasonically treating for 90 minutes at an ultrasonic power of 60 W to obtain a silica-alumina sol composite. The particle sizes of the nano-silica sol and the nano-alumina sol are both distributed between 10 and 20 nm, and the solid contents of the nano-silica sol and the nano-alumina sol are both 50%.
[0060] (4) adding the nanoparticle stabilizer to the silica-alumina sol complex and stirring evenly to obtain a modified silica-alumina sol complex, then adding the complex to the simulated seawater and stirring evenly, and then adding the mixed powder and the water reducing agent and stirring evenly to obtain a gelling material.
[0061] Performance test: The same method as in Example 1 was used to test the compressive strength of the test pieces of the cementitious material prepared in this example at ages of 1d, 28d, and 100d, the compressive strength retention rate of the test piece at age of 28 after being immersed in seawater for 100 days, the chloride ion migration coefficient, and the water-soluble chloride ion content of the cementitious material after hardening, and the percentage of the content of the chloride ion in the mass of the cementitious material was calculated. The test results of the above performance indicators are shown in Table 4 below.
[0062] It can be seen that the new self-adaptive cementitious material for seawater mixing prepared in this embodiment has the characteristics of high early strength, steadily improved later strength, strong chloride ion curing ability, and strong resistance to chloride ion and sulfate ion corrosion, showing excellent durability and resistance to seawater erosion.
[0063] Table 4
[0064]
[0065] Example 4
[0066] The preparation of a novel self-adaptive cementitious material for seawater mixing includes the following steps:
[0067] (1) Take the following raw material components: 50 parts by weight of 42.5 ordinary Portland cement, 30 parts by weight of auxiliary cementitious materials, 10 parts by weight of high-belite calcium sulfoaluminate cement clinker, 1 part by weight of polycarboxylic acid water reducer, 5 parts by weight of nanoparticle stabilizer, and 40 parts by weight of simulated seawater as shown in Table 1 above. Among them: the fineness of the cement (200 mesh sieve residue) is 1.3%, the auxiliary cementitious material is 200 mesh slag powder. The nanoparticle stabilizer is cocoamidopropyl betaine.
[0068] (2) The silicate cement, auxiliary cementitious material and high-belite calcium sulfoaluminate cement clinker are mixed and stirred for 5 minutes to obtain a mixed powder for use.
[0069] (3) adding the nanoparticle stabilizer to the simulated seawater and stirring evenly, and then adding the mixed powder and the water reducing agent and stirring evenly to obtain a gelling material.
[0070] Performance test: The same method as in Example 1 was used to test the compressive strength of the test pieces of the cementitious material prepared in this example at ages of 1d, 28d, and 100d, the compressive strength retention rate of the test piece at age of 28 after being immersed in seawater for 100 days, the chloride ion migration coefficient, and the water-soluble chloride ion content of the cementitious material after hardening, and the percentage of the content of the chloride ion in the mass of the cementitious material was calculated. The test results of the above performance indicators are shown in Table 5 below.
[0071] Table 5
[0072]
[0073] Example 5
[0074] The preparation of a novel self-adaptive cementitious material for seawater mixing includes the following steps:
[0075] (1) Take the following raw material components: 70 parts by weight of 42.5 ordinary Portland cement, 10 parts by weight of high-belite calcium sulfoaluminate cement clinker, 5 parts by weight of high-belite calcium ferroaluminate cement clinker, 14 parts by weight of silica-alumina sol complex, 3 parts by weight of polycarboxylate water reducer, 7 parts by weight of nanoparticle stabilizer, and 50 parts by weight of simulated seawater as shown in Table 1 above. Among them, the fineness of the cement (200 mesh residue) is 1.3%, the auxiliary cementitious material is fly ash with a fineness of 400 mesh, and the nanoparticle stabilizer is cocamidopropyl ammonium hydroxysulfonate.
[0076] (2) The silicate cement and high-belite calcium aluminoferrocene cement clinker are mixed and stirred for 5 minutes to obtain a mixed powder for later use.
[0077] (3) Mixing nano-silica sol and nano-alumina sol in a mass ratio of 0.5:1.5 and then ultrasonically treating for 30 minutes at an ultrasonic power of 100 W to obtain a silica-alumina sol composite. The particle sizes of the nano-silica sol and the nano-alumina sol are both distributed between 10 and 20 nm, and the solid contents of the nano-silica sol and the nano-alumina sol are both 20%.
[0078] (4) adding the nanoparticle stabilizer to the silica-alumina sol complex and stirring evenly to obtain a modified silica-alumina sol complex, then adding the complex to the simulated seawater and stirring evenly, and then adding the mixed powder and the water reducing agent and stirring evenly to obtain a gelling material.
[0079] Performance test: The same method as in Example 1 was used to test the compressive strength of the test pieces of the cementitious material prepared in this example at ages of 1d, 28d, and 100d, the compressive strength retention rate of the test piece at age of 28 after being immersed in seawater for 100 days, the chloride ion migration coefficient, and the water-soluble chloride ion content of the cementitious material after hardening, and the percentage of the content of the chloride ion in the mass of the cementitious material was calculated. The test results of the above performance indicators are shown in Table 6 below.
[0080] Table 6
[0081]
[0082] Example 6
[0083] The preparation of a novel self-adaptive cementitious material for seawater mixing includes the following steps:
[0084] (1) Take the following raw material components: 30 parts by weight of 42.5 ordinary Portland cement, 20 parts by weight of auxiliary cementitious material, 6 parts by weight of silica-alumina sol complex, 2 parts by weight of sodium lignin sulfonate water reducer, 3 parts by weight of nanoparticle stabilizer, and 28 parts by weight of simulated seawater as shown in Table 1 above. Among them, the fineness of the cement (200 mesh residue) is 1.3%, the auxiliary cementitious material is silica fume, and the nanoparticle stabilizer is alkyl acyl imidazoline.
[0085] (2) The silicate cement and the auxiliary cementitious material are mixed and stirred for 5 minutes to obtain a mixed powder for use.
[0086] (3) Mixing nano-silica sol and nano-alumina sol in a mass ratio of 1.5:0.5 and then ultrasonically treating for 90 minutes at an ultrasonic power of 60 W to obtain a silica-alumina sol composite. The particle sizes of the nano-silica sol and the nano-alumina sol are both distributed between 10 and 20 nm, and the solid contents of the nano-silica sol and the nano-alumina sol are both 50%.
[0087] (4) adding the nanoparticle stabilizer to the silica-alumina sol complex and stirring evenly to obtain a modified silica-alumina sol complex, then adding the complex to the simulated seawater and stirring evenly, and then adding the mixed powder and the water reducing agent and stirring evenly to obtain a gelling material.
[0088] Performance test: The same method as in Example 1 was used to test the compressive strength of the test pieces of the cementitious material prepared in this example at ages of 1d, 28d, and 100d, the compressive strength retention rate of the test piece at age of 28 after being immersed in seawater for 100 days, the chloride ion migration coefficient, and the water-soluble chloride ion content of the cementitious material after hardening, and the percentage of the content of the chloride ion in the mass of the cementitious material was calculated. The test results of the above performance indicators are shown in Table 7 below.
[0089] Table 7
[0090]
[0091] Example 7
[0092] The preparation of a novel self-adaptive cementitious material for seawater mixing includes the following steps:
[0093] (1) Take the following raw material components: 70 parts by weight of 42.5 ordinary Portland cement, 50 parts by weight of auxiliary cementitious materials, 10 parts by weight of high-belite calcium sulfoaluminate cement clinker, 5 parts by weight of high-belite calcium ferroaluminate cement clinker, 14 parts by weight of silica-alumina sol complex, 3 parts by weight of polycarboxylate water reducer, and 50 parts by weight of simulated seawater as shown in Table 1 above. Among them, the fineness of the cement (200 mesh sieve residue) is 1.3%, and the auxiliary cementitious material is fly ash with a fineness of 400 mesh.
[0094] (2) The silicate cement, auxiliary cementitious material and high-belite calcium sulfoaluminate cement clinker are mixed and stirred for 5 minutes to obtain a mixed powder for use.
[0095] (3) Mixing nano-silica sol and nano-alumina sol in a mass ratio of 0.5:1.5 and then ultrasonically treating for 30 minutes at an ultrasonic power of 100 W to obtain a silica-alumina sol composite. The particle sizes of the nano-silica sol and the nano-alumina sol are both distributed between 10 and 20 nm, and the solid contents of the nano-silica sol and the nano-alumina sol are both 20%.
[0096] (4) adding the silica-alumina sol complex to the simulated seawater and stirring evenly, and then adding the mixed powder and the water reducing agent and stirring evenly to obtain a gelling material.
[0097] Performance test: The same method as in Example 1 was used to test the compressive strength of the test pieces of the cementitious material prepared in this example at ages of 1d, 28d, and 100d, the compressive strength retention rate of the test piece at age of 28 after being immersed in seawater for 100 days, the chloride ion migration coefficient, and the water-soluble chloride ion content of the cementitious material after hardening, and the percentage of the content of the chloride ion in the mass of the cementitious material was calculated. The test results of the above performance indicators are shown in Table 8 below.
[0098] Table 8
[0099]
[0100] Example 8
[0101] The preparation of a novel self-adaptive cementitious material for seawater mixing includes the following steps:
[0102] (1) Take the following raw material components: 50 parts by weight of 42.5 ordinary Portland cement, 30 parts by weight of auxiliary cementitious materials, 10 parts by weight of high-belite calcium sulfoaluminate cement clinker, 10 parts by weight of nano-silica sol, 1 part by weight of polycarboxylic acid water reducer, 5 parts by weight of nano-particle stabilizer, and 40 parts by weight of simulated seawater as shown in Table 1 above. Among them: the fineness of the cement (200 mesh sieve residue) is 1.3%, the auxiliary cementitious material is 200 mesh slag powder. The nano-particle stabilizer is cocoamidopropyl betaine. The particle size distribution of the nano-silica sol is between 10 and 20 nm, and the solid content of the nano-silica sol is 45%.
[0103] (2) The silicate cement, auxiliary cementitious material and high-belite calcium sulfoaluminate cement clinker are mixed and stirred for 5 minutes to obtain a mixed powder for use.
[0104] (3) adding the nanoparticle stabilizer to the nano-silica sol and stirring evenly to obtain a modified silica sol, then adding the modified silica sol to the simulated seawater and stirring evenly, and then adding the mixed powder and the water reducing agent and stirring evenly to obtain a gelling material.
[0105] Performance test: The same method as in Example 1 was used to test the compressive strength of the test pieces of the cementitious material prepared in this example at ages of 1d, 28d, and 100d, the compressive strength retention rate of the test piece at age of 28 after being immersed in seawater for 100 days, the chloride ion migration coefficient, and the water-soluble chloride ion content of the cementitious material after hardening, and the percentage of the content of the chloride ion in the mass of the cementitious material was calculated. The test results of the above performance indicators are shown in Table 9 below.
[0106] Table 9
[0107]
[0108] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A new self-adaptive cementitious material for seawater mixing, characterized in that: The invention comprises the following components: 30-70 parts by weight of silicate cement, 20-50 parts by weight of auxiliary cementitious material, 5-15 parts by weight of high-belite calcium sulfoaluminate cement clinker and / or high-belite calcium ferroaluminate cement clinker, 6-14 parts by weight of silica-alumina sol complex, 1-3 parts by weight of water reducer, 3-7 parts by weight of nano-particle stabilizer and 28-50 parts by weight of mixing water; the silica-alumina sol complex comprises nano silica sol and nano aluminum sol at the same time, and the silica sol is connected with the two sol particles by dehydration condensation of Si-OH on the surface of the silica sol and -COOH on the surface of the aluminum sol to form -COO-.
2. The self-adaptive new gelling material for seawater mixing according to claim 1 is characterized in that: The auxiliary cementitious material includes at least one of slag powder, fly ash and ultrafine powder; optionally, the fineness of the auxiliary cementitious material is 200-400 meshes.
3. The self-adaptive new gelling material for seawater mixing according to claim 1, characterized in that: The mass ratio of the nano-silica sol to the nano-alumina sol is 0.5-1.5:0.5-1.5; optionally, the particle size of the nano-silica sol is 10-20 nm.
4. The self-adaptive new gelling material for seawater mixing according to claim 1, characterized in that: The solid contents of the nano silica sol and the nano aluminum sol are both 20-50%.
5. The new self-adaptive gelling material for seawater mixing according to any one of claims 1 to 4, characterized in that: The water reducer includes at least one of a polycarboxylate water reducer, a naphthalene-based water reducer, and a lignin sulfonate water reducer.
6. The new self-adaptive gelling material for seawater mixing according to claim 5, characterized in that: The nanoparticle stabilizer includes at least one of cocamidopropyl betaine, cocamidopropyl ammonium hydroxysulfonate, and alkyl acyl imidazoline.
7. The new self-adaptive gelling material for seawater mixing according to any one of claims 1 to 4, characterized in that: The mixing water includes at least one of fresh water and sea water.
8. The method for preparing the new self-adaptive gelling material for seawater mixing according to any one of claims 1 to 7, characterized in that: The steps include: (1) mixing the silicate cement, auxiliary cementitious materials, high-belite calcium sulfoaluminate cement clinker and / or high-belite calcium ferroaluminate cement clinker to obtain a mixed powder for standby use; (2) mixing the nano-silica sol and the nano-alumina sol and subjecting them to ultrasonic treatment to obtain a silica-alumina sol composite, wherein the silica sol is dehydrated and condensed by Si-OH on its surface and -COOH on the surface of the aluminum sol to form -COO- to connect the two sol particles; (3) The nanoparticle stabilizer is added to the silica-alumina sol complex and mixed to obtain a modified silica-alumina sol complex, and then the complex is added to the mixing water and mixed, and then the mixed powder and the water reducing agent are added and mixed to obtain a cementitious material.
9. The method for preparing the new self-adaptive gelling material for seawater mixing according to claim 8, characterized in that: In step (2), the ultrasonic treatment time is 30 to 90 minutes, and the ultrasonic power is 60 to 100W.
10. Use of the new self-adaptive cementitious material for seawater mixing as claimed in any one of claims 1 to 7, or the new self-adaptive cementitious material for seawater mixing obtained by the preparation method of claim 8 or 9 in marine engineering, water conservancy engineering, hydropower engineering or bridge engineering.
Citation Information
Patent Citations
Ornamental articles having coating membrane
CA1294836C
II-type polymer cement waterproofing coating modified by nano materials and preparation method thereof
CN101550309A
Aqueous concrete seal hardener and preparation method thereof
CN102030560A
Close packing high-performance cement-based fiber composite product and production method thereof
CN102701651A
High-anticorrosion composite Portland cement and production method thereof
CN109020270A